GLOBAL SAFETY IN THE PUBLIC HEALTHCARE IN THE XXI CENTURY - article editorial (Union of pediatricians of Russia, 2008)
We are presenting one of the chapters from the who report devoted to critical emergencies of international importance in the public healthcare, the most frightful of which is still pandemic flu. The counter measures in respect of the given threat are preemptive. They give a chance to get ready for the pandemic and probably prevent the threat from coming true.Key words: influenza pandemic, bird flu, prevention, who global strategy.